U.S. manure methane emissions represent a greater contributor to implied climate warming than enteric methane emissions using the global warming potential* methodology - Matthew R. Beck; Logan R. Thompson; Jason E. Rowntree; Terra N. Thompson; Jacek A. Koziel; Sara E. Place; Kim R. Stackhouse-Lawson (Frontiers in Sustainable Food Systems, 2023)
IntroductionIt is important to relate different greenhouse gas (GHG) emissions to a carbon dioxide (CO2) equivalence (CO2-e) basis. This is typically done by multiplying the emissions of a GHG by its global warming potential (GWP), usually on a 100-year basis (GWP100). For methane (CH4), the predominant GHG from livestock production, the GWP100 value is 28. The GWP100 method has been shown to not adequately relate CH4 emissions to actual climate warming due to CH4′s short atmospheric lifespan (~12 years). As such, a newer method has been developed, termed GWP*. This method relates current emission rates to previous emission rates, typically on a 20-year time horizon. To date, the implications of using GWP* rather than GWP100 have not been discussed for manure emissions and have not been discussed for enteric and manure emissions relative to different livestock species or geographical regions of the United States.MethodsUsing emission estimate data from the U.S. Environmental Protection Agency (EPA), we assessed how national manure and enteric CH4 emissions changed from 1990 to 2020.ResultsThe average rate of change was analyzed by regression. Enteric CH4 emissions remained relatively constant with a non-significant slope (P = 0.51), whereas manure CH4 emissions have been increasing (P < 0.01; R2 = 0.96) by 0.03-MMT/year. Furthermore, investigation demonstrated that the increase in manure CH4 emissions was largely driven by the dairy (25.9-kt increase in manure CH4 per year; P < 0.01; R2 = 0.98) and swine (5.4-kt increase in manure CH4 per year; P < 0.01; R2 = 0.50) industries. Due to the increasing emission estimates, manure CH4 [90.8-MMT CO2-warming equivalence (CO2-we) on average] was a larger contributor to climate warming than enteric CH4 (89.2-MMT CO2-we on average) from 2010 through 2020, when calculated with the GWP* methodology. This stands in contrast to the GWP100 methodology, which suggests that enteric CH4 emissions (191-MMT CO2-e) from 2010 to 2020 were on average 206% greater contributors to warming than manure CH4 emissions (62.3-MMT CO2-e).DiscussionThese results suggest that manure CH4 emissions may be contributing more to climate warming than enteric CH4, and more effort may be required to mitigate this source of emissions.